Empowering High School Students: The Impact of Group Self-Compassion Interventions on Anxiety Tendencies - Andhita, Nadya; Boediman, Lia Mawarsari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Anxiety disorders are the most prevalent mental health issues among adolescents worldwide. These issues can make it hard for individuals to control their fear of future events, and they can lead to a decline in physical, cognitive, social relationships, and occupational functions. This study aims to assess the effectiveness of group intervention based on self-compassion principles in reducing anxiety levels among high school adolescents. Self-compassion involves having a kind and understanding attitude towards oneself when facing suffering. The intervention was conducted in a group setting because adolescents often find it easier to relate and learn from their peers. This study suggests that group intervention based on self-compassion principles can increase self-compassion levels and decrease anxiety levels in high school adolescents. However, the significance of the quantitative changes remains inconsistent. Factors such as participants’ intrinsic motivation, commitment to attendance, school support, group cohesiveness, and the facilitator’s role in improving therapeutic group dynamics need to be evaluated to enhance the effectiveness of this group intervention. Gangguan kecemasan merupakan masalah kesehatan mental yang paling umum di kalangan remaja di seluruh dunia. Gangguan ini dapat berdampak negatif bagi individu dalam mengendalikan rasa takut terhadap kejadian di masa depan, serta menyebabkan penurunan fungsi fisik, kognitif, hubungan sosial, dan pekerjaan. Penelitian ini bertujuan untuk melihat efektivitas intervensi kelompok berbasis prinsip-prinsip self-compassion dalam mengurangi tingkat kecemasan di kalangan remaja SMA. Self-compassion atau dalam bahasa Indonesia disebut welas diri adalah sikap yang penuh kebaikan dan pengertian terhadap diri sendiri ketika menghadapi penderitaan. Intervensi pada penelitian ini dilakukan dalam kelompok karena remaja seringkali lebih mudah mengidentifikasi diri dan belajar dari teman sebaya. Penelitian ini menunjukkan bahwa intervensi kelompok berbasis prinsip-prinsip self-compassion dapat meningkatkan tingkat self-compassion dan menurunkan tingkat kecemasan pada remaja SMA. Namun, signifikansi perubahan secara kuantitatif masih inkonsisten. Faktor-faktor seperti motivasi intrinsik peserta, komitmen terhadap kehadiran, dukungan dari guru-guru sekolah, kohesivitas kelompok, serta peran fasilitator dalam meningkatkan dinamika kelompok yang terapeutik perlu dievaluasi untuk meningkatkan efektivitas intervensi kelompok ini.